International Involvement in Sovereign States: The Role of the AU in the Preservation of Peace and Security in Sub-Saharan Africa: The Case of Cameroon - (:unkn) unknown (My University, 2023)
The Anglophone issue, the jihadist insurgency, and Boko Haram are among the several violent conflicts that are occurring in Cameroon, along with escalating ethnic and political tensions both online and offline. Nevertheless, the Responsibility to Protect (R2P) tenet has been steadily adopted across Africa. This study's primary goal was to learn what the African Union (AU) is doing in connection to the peace and security situation in Cameroon in light of the above context. This study was descriptive in nature. Secondary data was the sole form of data used in this investigation. Information was gathered through the internet, periodicals, newspapers, books, journals, and other sources. Numerous studies show that the AU Peace and Security Council, which makes decisions on the prevention, management and resolution of conflicts, do not address Cameroon's challenges and problems. Therefore the AU and the United Nations (UN) can coordinate their efforts in addressing the humanitarian needs of refugees and displaced people.
Keywords: African Research